Acute effect of intermittent and continuous aerobic exercise on release of cardiac troponin T in sedentary men. (1st June 2017) - Ranjbar, Rouhollah; Ahmadi, Mohammad Amin; Zar, Abdossaleh; Krustrup, Peter
Abstract: Background: Studies have shown that acute exercise can increase serum concentrations of cardiac biomarkers, including cardiac troponin T (cTnT). We investigated the acute effects of intermittent (IE) and continuous (CE) exercise at the same cardiac workload on myocardial necrosis biomarkers in sedentary men. Methods: Eleven sedentary healthy men aged 22.3 ± 1.9 years completed the study. The subjects were divided into two groups and performed, in random order, IE (intensity alternating between 50% (2 min) and 80% (1 min) HRreserve) or CE (60% HRreserve). The study was designed as a single-blinded randomised crossover trial performed on two distinct experimental days separated by a 1-week washout period. Each session consisted of 40 min of aerobic exercise, either IE or CE, on a treadmill. Blood samples were taken before (PRE), immediately after (POST) and 1 h after (POST-1) each exercise session. Results: hs-cTnT significantly increased immediately after exercise in both protocols and remained elevated at POST-1 (P < 0.05). There was no significant difference between POST and POST-1 values(P > 0.05). Neither CE nor IE caused any significant change in CK-MB (P > 0.05). The results also showed that HR and RPP increased significantly following both exercise protocols (P = 0.001). Conclusions: In summary, both CE and IE results in increased serum concentrations of hs-cTnT in sedentary men. However, this increase does not seem to be caused by the irreversible death of cardiomyocytes. CE resulted in a greater hs-cTnT concentration than IE.